Republicans and Democrats: Who has a voice on Twitter? The case of the 2016 US Presidential Elections - Rodrigues, Judite (2017)
Twitter has become a space for political deliberation and confrontational positions, during election time. Therefore, the prime objective of this research focused on understanding which U.S. political force – republicans or democrats – had a more substantial presence on Twitter, during the presidential election of 2016. As we were trying to decipher this issue, we were also trying to understand the power of the hashtag in political communication on Twitter for each political perspective. For this, we collected and analysed 4399 tweets. In this paper, we observed that the presence of the republicans was more prominent than the democrats. However, the true voice of Twitter is the common citizen. We verified that, in this social media, the hashtag is much more than an aggregator of content. This mechanism of participation respects the objective of expressing a political position too.